PolitePEER: does peer review hurt? A dataset to gauge politeness intensity in the peer reviews. - Bharti, Prabhat Kumar; Navlakha, Meith; Agarwal, Mayank; Ekbal, Asif (Language Resources & Evaluation, 2024)
Even though peer review is a central aspect of scientific communication, research shows that the process reveals a power imbalance. The position of the reviewer allows them to be harsh and intentionally offensive without being held accountable. It casts doubt on the integrity of the peer-review process and transforms it into an unpleasant and traumatic experience for authors. Accordingly, more effort should be given to provide critical and constructive feedback. Hence, it is necessary to remedy the growing rudeness and lack of professionalism in the review system, by analyzing the tone of review comments and creating a classification on the level of politeness in a review comment. To this end, we develop the first annotated PolitePEER dataset encompassing five levels of politeness: (1) highly impolite, (2) impolite, (3) neutral, (4) polite, and (5) highly polite. The review sentences accrued from multiple venues, viz., ICLR, NeurIPS, Publons and ShitMyReviewersSay. We have formulated our annotation guidelines and conducted a thorough analysis of the PolitePEER dataset, ensuring the dataset quality with an inter-annotation agreement of 93%. Additionally, we have benchmarked PolitePEER for multiclass classification and provided an extensive analysis of the proposed baseline. As a result, the proposed PolitePEER can aid in developing a politeness indicator to notify the reviewer and the editors to amend and formalize the review accordingly. Our dataset and codes are available at https://github.com/PrabhatkrBharti/PolitePEER.git for the community to explore further.